Blinded by the Spite? Path Model of Political Attitudes, Selectivity, and Social Media. Issue 3 (27th May 2017) - Johnson, Thomas J.; Kaye, Barbara K.; Lee, Angela M.
ABSTRACT: Despite fears that selective exposure and selective avoidance could deepen polarization and negatively affect the democratic process, few studies have directly studied this phenomenon. This study explores whether selective exposure and avoidance to blogs, social network sites, and Twitter directly influence confidence in Congress and the president or more indirectly through polarization. This study suggests that fears of selective exposure, selective avoidance, and polarization infecting the democratic process appear overstated. First, polarization was positively related to confidence in Congress and the president. Second, selective exposure to social media sites strengthens confidence in the president and in Congress. Twitter boosts confidence in Congress. Third, selective avoidance had a negative influence on other measures, which suggests people seek both information that challenges their views as well as ones that supports them. Finally, selective exposure and avoidance proved weak indicators of polarization. Instead, strength of partisanship is the stronger predictor of confidence in Congress and the president.